2016
DOI: 10.1186/s12914-016-0103-1
|View full text |Cite
|
Sign up to set email alerts
|

Is the UN Convention on the Rights of Persons with Disabilities Impacting Mental Health Laws and Policies in High-Income Countries? A Case Study of Implementation in Canada

Abstract: BackgroundPersons with psychosocial disabilities face disparate access to healthcare and social services worldwide, along with systemic discrimination, structural inequalities, and widespread human rights abuses. Accordingly, many people have looked to international human rights law to help address mental health challenges. On December 13, 2006, the United Nations formally adopted the Convention on the Rights of Persons with Disabilities (CRPD) – the first human rights treaty of the 21st century and the fastes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…This trend is backed by political campaigns and agreements like the United Nations Convention on the Rights of Persons with Disabilities (United Nations, 2006) or a European Union project with the title ‘The right to political participation of persons with mental health problems and persons with intellectual disabilities’ (Fundamental Rights Agency (FRA) – Euro-pean Union Agency for Fundamental Rights, 2010). Within the last years, considerable effort has been made to reduce restrictive measures in mental health settings (Hoffman, Sritharan, & Tejpar, 2016; McSherry, 2013; Morrissey, 2012; Steinert et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This trend is backed by political campaigns and agreements like the United Nations Convention on the Rights of Persons with Disabilities (United Nations, 2006) or a European Union project with the title ‘The right to political participation of persons with mental health problems and persons with intellectual disabilities’ (Fundamental Rights Agency (FRA) – Euro-pean Union Agency for Fundamental Rights, 2010). Within the last years, considerable effort has been made to reduce restrictive measures in mental health settings (Hoffman, Sritharan, & Tejpar, 2016; McSherry, 2013; Morrissey, 2012; Steinert et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…That was a period when mental disorders (disability) were treated exclusively as a defect, i.e., damage on the part of an individual who needs appropriate care and assistance, which justifies medical intervention. 12 The existing legal framework for treating people with mental disabilities was reduced in practice to a mere formalism in which the physicians had wide discretion. This, unfortunately, led to a series of abuses to the detriment of psychiatric patients.…”
Section: Obligation Of the State Parties To Implement "The Paradigm Of Presumed Legal Capacity" And Challenges Aheadmentioning
confidence: 99%
“…53 Given such a small number of reservations in relation to the total number of State Parties, it could be concluded that, at the time when they were able to formulate a reservation, states did not see anything controversial in Art. 12 their national legislative framework to be fully compliant with the CRPD provision.…”
Section: State Parties' Attitude Toward the Provision Of Art 12mentioning
confidence: 99%
“…The grounds on which mandatory detention orders can be issued vary from region to region, but orders are generally based on risk assessments of harm "to self or others. " While it is recognized that domestic mental health laws operate in contravention of the UNCRPD 1 (Pũras, 2017(Pũras, , 2018Hoffman et al, 2016), there has been little political will to bring domestic laws in line with international law.…”
Section: Mental Health Human Rights and Social Justicementioning
confidence: 99%